2012
DOI: 10.1007/s00464-011-2074-6
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo pig training model for esophageal endosopic submucosal dissection (ESD) for endoscopists with experience in gastric ESD

Abstract: This original ex vivo training model was helpful to endoscopists with experience in gastric ESD in acquiring the basic skills for performing esophageal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…In ESD, a clinical situation can be easily simulated by making artificial lesions at preferred sites, and the usefulness of ESD training models using a porcine stomach has been demonstrated in many studies [5,6]. However, no studies have reported training models for treating esophageal varices.…”
Section: Discussionmentioning
confidence: 99%
“…In ESD, a clinical situation can be easily simulated by making artificial lesions at preferred sites, and the usefulness of ESD training models using a porcine stomach has been demonstrated in many studies [5,6]. However, no studies have reported training models for treating esophageal varices.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models could be used not only for training in gastric ESD but also for esophageal and colonic ESD [66][67][68][69] . Tanaka et al [67] developed an original training model for esophageal ESD using isolated pig esophagus and assessed this ex-vivo model in endoscopists with experience in gastric ESD.…”
Section: Esd Training In the Westmentioning
confidence: 99%
“…Tanaka et al [67] developed an original training model for esophageal ESD using isolated pig esophagus and assessed this ex-vivo model in endoscopists with experience in gastric ESD. The operation time and number of muscularis propria layer injuries decreased gradually as endoscopists gained training experience, while the mean number of muscularis propria layer injuries significantly decreased for all of the endoscopists in the latter period compared with the former period.…”
Section: Esd Training In the Westmentioning
confidence: 99%
“…A specific model for esophageal ESD has been described recently 13. A double overtube system was used to make the model more stable and to prevent the esophagus from sliding with the movements of the endoscope.…”
Section: Ex Vivo Modelmentioning
confidence: 99%